PENERAPAN PENDEKATAN PROBLEM SOLVING MODEL SSCS (SEARCH, SOLVE, CREATE, AND SHARE) DAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DI SMP MUHAMMADIYAH 8 BATU - Try Soni Jaohari; Moh. Mahfud Effendi; Siti Inganah (Program Studi Pendidikan Matematika, Universitas Muhammadiyah Kupang, 2021)
This research in order to describe: 1) the implementation of problem solving approach type SSCS (search, solve, create, and share) on mathematics lesson; and 2) the students mathematical communications ability on implementation of problem solving approach type SSCS (search, solve, create, and share) on Muhammadiyah Junior High School of 8 Batu. The research type is descriptive with qualitative approaching. The research object is students mathematical communication ability in implementation of problem solving approach type SSCS (search, solve, create, and share). Data sources taken from all of students in the class with twenty persons there. The procure technique is by using observation and test. Data is taken by observation in order to get of students activity and students communication ability in verbal, and test session in order to get of students communication ability in writing. Data anilisys is by recon up totallity percentage for each indicator and totality percentage of achievement studens activity and totality percentage of student communication ability. The results of this research shows us that: 1) implementation of problem solving approach type SSCS (search, solve, create, and share) based students activity is â€œgoodâ€ and has undergone in a line nased of all phases and include to learning steps in each phase. However, students still dependence of teacherâ€™s explanation like usually, while student isnâ€™t given in this approach. There for, this approach must be continue in the next so that get of maximum learning outcomes; 2) students communication ability in verbal and written in implementation of problem solving approach type SSCS (search, solve, create, and share) is â€œgoodâ€. However, students still need more times to practice in solve other mathematic problems, expecially on find out or write mathematic ideas.